Internal auditing function and performance of state departments in the upper eastern region of Kenya - Kendi, Doreen (Meru, Doreen Kendi, 2021)
State department are spread throughout the country and in particular, in every sub county where they represent their respective ministries at local level. Each department is required to adhere to the stipulated guidelines, be accountable to the state on the funding, safeguard resources and use them economically and effectively against stated objectives while ensuring risks are appropriately identified, analyzed and managed. To ensure compliance and accountability, the national treasury has put in place the internal auditing function to ensure compliance by all Authority to Incur Expenditure (AIE) holders with all requirement as provided for in the Public Financial Management Act. This study therefore intended to evaluate how effective the internal audit function has been in enhancing performance of the state departments. This study used research questions. The findings were expected to be of importance to AIE holders, clients, the general public and state. The study was guided by various theories, namely, the agency theory, contingent theory and stewardship theory. The independent variables as conceptualized are represented diagrammatically. The study adopted a survey design targeting all the state departments in all sub counties in the upper Eastern region of Kenya (Meru, Tharaka Nithi,Embu, Isiolo and Marsabit counties).All the 276 departments heads, otherwise called Authority to Incur Expenditure (AIE) holders were included in the study. However, a representative sample of 110 respondents were obtained using stratified random sampling. Data was collected using a self-administered questionnaire. A pilot study was conducted by using 10 questionnaires to the members of the population who were not in the sample. The instrument was validated by seeking expert opinion. Data was analyzed using descriptive analysis and correlation analysis. The analyzed data was presented using tables and pie charts. The study established a strong positive relationship correlation between the independent variables (risk management, fraud detection and evaluation of internal controls) and the dependent variables (department performance). In addition, the internal audit function was found to have influence on identification of risks, and that the advisory and consultancy role of the internal auditors was significantly crucial in maintaining departmental risks below the threshold. It was concluded that all three independent variables had positive influence on the dependent variable. There was general trend of improvement in performance of the dependent various departments over three years$1 (Bperiod. It was recommended that departmental managers should ensure risk mitigation measures are functional all the time.s